2019
DOI: 10.1037/xlm0000711
|View full text |Cite
|
Sign up to set email alerts
|

A valence asymmetry in predecisional distortion of information: Evidence from an eye tracking study with incentivized choices.

Abstract: Existing research shows that the order in which evidence arrives can bias its evaluation and the resulting decision in favor of information encountered early on. We used eye-tracking to study the underlying cognitive mechanisms in the context of incentivized financial choices based on real world market data. Subjects learned about the presence/absence of a transaction fee, before seeing expert opinions regarding an investment prospect and deciding whether to invest. Although the fee had no effect on the proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
(76 reference statements)
1
2
0
Order By: Relevance
“…In particular, an alternative to our “Waddington landscape” intuition might be that having more information increases the cognitive load, making subsequent top-down control of attention harder, more imprecise, and the scanpaths more irregular. This explanation would be consistent with the fact that scanpaths are more idiosyncratic after a negative than after a positive disclosure, as we previously found that negative early information increases the subsequent cognitive effort (M. Król & Król, 2019c).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In particular, an alternative to our “Waddington landscape” intuition might be that having more information increases the cognitive load, making subsequent top-down control of attention harder, more imprecise, and the scanpaths more irregular. This explanation would be consistent with the fact that scanpaths are more idiosyncratic after a negative than after a positive disclosure, as we previously found that negative early information increases the subsequent cognitive effort (M. Król & Król, 2019c).…”
Section: Discussionsupporting
confidence: 85%
“…This was further adjusted by a random amount independent of the return: either ϩ15 ("positive adjustment") or Ϫ25 ("negative adjustment"). These values were set vis-a `-vis the mean return of ϩ37, based on previous experiments with similarly designed stimuli (M. Król & Król, 2019c), so that disclosing the adjustment beforehand would not make either investing or refraining the obvious choice, discouraging from examining opinions (that is, there was still a small riskpremium under a negative adjustment, but the positive one was small enough so as not to induce people to invest regardless of the opinion words).…”
Section: Designmentioning
confidence: 99%
“…For example, Hinvest et al (2018) addressed the conflict between investment and social preferences and determined that it was possible to nudge and classify investors using images related to social behavior and negative social images, eliciting a stronger effect than positive ones. Król and Król (2019a) found that the initial positive information shown to subjects in a stock trading experiment facilitates the elaboration of further positive information; this effect is not present for negative information. As such, positive information has a stronger effect on participants' decisions.…”
Section: Literature Reviewmentioning
confidence: 91%